2009
DOI: 10.1017/s0029665109001050
|View full text |Cite
|
Sign up to set email alerts
|

Changing health behaviour of young women from disadvantaged backgrounds: evidence from systematic reviews

Abstract: Observational evidence suggests that improving the diets of women of child-bearing age from disadvantaged backgrounds might be an important component of public health strategies aimed at reducing the burden of chronic disease in their offspring. The development of an intervention to improve the nutrition of young women needs to be informed by a systematic collation of evidence. Such a systematic collation of evidence from systematic reviews of interventions directed at changing health behaviours including diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 20 publications
0
33
0
Order By: Relevance
“…Reviews of evidence have shown that interventions with certain features are more likely to improve health behaviors for disadvantaged women. These include: providing information on risks and benefits of health behaviors; goal-setting; and continued support after the initial intervention [51,52]. The evidence indicates that there is a need for empowerment approaches that work by improving the self-efficacy of participants.…”
Section: Interventionsmentioning
confidence: 99%
“…Reviews of evidence have shown that interventions with certain features are more likely to improve health behaviors for disadvantaged women. These include: providing information on risks and benefits of health behaviors; goal-setting; and continued support after the initial intervention [51,52]. The evidence indicates that there is a need for empowerment approaches that work by improving the self-efficacy of participants.…”
Section: Interventionsmentioning
confidence: 99%
“…Social support interventions for low-income women who smoke have been shown to have a positive impact on smoking reduction or cessation as well as other outcome measures, such as coping, social network, and health behaviors (Andrews, 2004;Baird, Cooper, Margetts, Barker, & Inskip, 2009;Stewart et al, 2010;Westmaas et al, 2010). Several studies among Aboriginal women and ethnic minority women have identified social support and community involvement as key components for addressing tobacco dependence (Andrews, 2004;Brothers & Borrelli, 2011;de Finney et al, 2013).…”
Section: Social Supportmentioning
confidence: 99%
“…Recent reviews of evidence have provided useful insights into the features of behaviour change interventions associated with effectiveness in low income groups and women of childbearing age: providing information on the risks and benefits of health behaviours combined with goal setting and continued support after the initial intervention was more likely to lead to behaviour change 18 19. Similarly, a review of interventions that were effective in improving health behaviours in populations considered at risk of developing diabetes found that interventions most likely to be effective were those that targeted both diet and physical activity.…”
Section: Introductionmentioning
confidence: 99%